Fischer–Tropsch synthesis: effect of ammonia on product selectivities for a Pt promoted Co/alumina catalyst. Issue 13 (24th January 2017) - Rao Pendyala, Venkat Ramana; Shafer, Wilson D.; Jacobs, Gary; Martinelli, Michela; Sparks, Dennis E.; Davis, Burtron H.
Abstract : The effects of co-fed ammonia in synthesis gas on the activity and product selectivities of a typical cobalt catalyst (0.5% Pt–25% Co/Al2 O3 ) were investigated during the Fischer–Tropsch synthesis using a continuously stirred tank reactor (CSTR). Abstract : The effects of co-fed ammonia in synthesis gas on the activity and product selectivities of a typical cobalt catalyst (0.5% Pt–25% Co/Al2 O3 ) were investigated during the Fischer–Tropsch synthesis using a continuously stirred tank reactor (CSTR). The product selectivities were compared at a similar CO conversion level for various concentrations (10–1000 ppmv) of ammonia, as well as clean (un-poisoned) conditions. The addition of 10–1000 ppmv ammonia (concentration of ammonia with respect to the syngas feed) significantly decreased activity; the percentage of deactivation was similar (∼40%) for the various concentrations of ammonia used. At similar CO conversions, the addition of ammonia caused an increase in olefin selectivity and the corresponding paraffin and alcohol selectivities were decreased compared to the ammonia free synthesis conditions. Olefin selectivity increased with increasing concentration of ammonia, and the paraffin and alcohol selectivities were decreased with increasing ammonia concentration. At similar CO conversions, ammonia addition exhibited a positive effect on hydrocarbon selectivity ( i.e., lower light gas products and higher C5 +) and also light gas product selectivities (C1 –C4 ) were decreased and C5 + selectivity increased with increasing concentration of ammonia compared to ammonia free conditions.